2020
DOI: 10.3390/antiox9020183
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Stress Markers in the Erythrocytes and Heart Muscle of Obese Rats: Relate to a High-Fat Diet but Not to DJOS Bariatric Surgery

Abstract: Obesity and high-fat diet (HF) are prevalent causes of oxidative stress (OS). Duodenal-jejunal omega switch (DJOS) is a bariatric procedure used for body mass reduction, extensively tested in animal models. We studied the long-term impact of bariatric surgery and an HF diet on the oxidative stress markers in erythrocytes and heart muscles of rats. We analyzed superoxide dismutase (SOD), catalase (CAT), glutathione transferase (GST), glutathione reductase (GR), glutathione peroxidase (GPx) activity and malondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 73 publications
3
26
0
Order By: Relevance
“…This intensifies mitochondrial energy metabolism, which enhances free radicals formation [ 12 , 13 ]. The intensity of oxidative stress can be assessed using various general and specific indicators [ 14 16 ]. Total antioxidant capacity (TAC) shows the interaction between synergistic and antagonistic antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…This intensifies mitochondrial energy metabolism, which enhances free radicals formation [ 12 , 13 ]. The intensity of oxidative stress can be assessed using various general and specific indicators [ 14 16 ]. Total antioxidant capacity (TAC) shows the interaction between synergistic and antagonistic antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important for extending the employment age and active longevity in the modern society in the context of the gradual increase of the retirement age across both the developed and developing countries. Thus, the analysis of big data, including various genetic, metabolic, and medical indicators associated with biological aging, demonstrated that dietary restrictions [ 15 , 16 ], weight loss, exercise [ 17 , 18 ], and even an improvement of the intestinal microbiota [ 19 , 20 , 21 , 22 ] can reverse the rise in markers of aging and prevent pathological conditions, including obesity, diabetes, cancers, etc., showing great promise for increasing the net average active life expectancy in the global population [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress refers to an imbalance between the antioxidants and reactive oxygen and nitrogen species (RONS) in a system in favor of these reactive species (Eleazu et al, 2020;Huang et al, 2015). It also reflects the negative impact the lack of balance between the prooxidant and antioxidant defense mechanisms of a system has on cells (Poloczek et al, 2020).…”
mentioning
confidence: 99%